Synthesis and Antimicrobial Activity of Some 2-(4',5'-Disubstituted Thiazolo)-1H-Isoindole-1,3(2H)-Diones/Succinimides - Rajpurohit, Sangeeta; Sah, Pramilla (Asian Journal of Chemistry, 2016)
4-substituted thiazole (I) derivatives were fused with 2-substituted-1H-isoindole-1,3(2H)-dione/succinic anhydride which converted to 2-(4'-substituted thiazolo)-1H-isoindole-1,3(2H)-dione (II) and 2-(4'-substituted thiazolo)succinimide (III). C-5 carbon of the thiazole nuclei was then blocked by acid chlorides of N-protected amino acids to give the final compound namely 2-[4'-substituted-5'-(2"-alkyl substituted acetylamidophenyl)thiazolo]-5'-(2"-alkyl substituted acetylamidophenyl)thiazolo]-1H-isoindole 1,3(2H)-diones (IV) and 2-[4'-substituted-5-(2"-alkyl substituted-acetylamido phenyl)thiazolo]succinimides (V). All the synthesized compounds were evaluated for antibacterial and antifungal activities.